2000
DOI: 10.1053/jhep.2000.19343
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Core Protein Activates the MAPK/ERK Cascade Synergistically With Tumor Promoter TPA, But Not With Epidermal Growth Factor or Transforming Growth Factor α

Abstract: Persistent hepatitis C virus (HCV) infection is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 30 publications
6
84
1
1
Order By: Relevance
“…Cells were treated by PD98059 (15-50 lM, Cell Signaling Technology (CST), Boston, MA, USA) or U0126 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) lM, CST) 24 h before harvest. ShRNAs were cloned into pLKO.1 lentiviral vectors using primers as follows: MEK1-sh#1-Forward: CCGGAACTCTGGATCAAGTCCTGAACTCGAGTTCAGGACTTGATCCA-GAGTTTTTTTG and Reward: AATTCAAAAAAACTCTGGATCAAGTC C TGAACTCGAGTTCAGGACTTGATCCAGAGTT; MEK1-sh#2-Forward: CCGGAAGGACTCATTACTCTGTGCACTCGAGTGCACAGAGTAATGAGT CCTTTTTTTG and Reward: AATTCAAAAAAAGGACTCATTACTCTG TGCACTCGAGTGCACAGAGTAATGAGTCCTT.…”
Section: Cell Culture and Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were treated by PD98059 (15-50 lM, Cell Signaling Technology (CST), Boston, MA, USA) or U0126 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) lM, CST) 24 h before harvest. ShRNAs were cloned into pLKO.1 lentiviral vectors using primers as follows: MEK1-sh#1-Forward: CCGGAACTCTGGATCAAGTCCTGAACTCGAGTTCAGGACTTGATCCA-GAGTTTTTTTG and Reward: AATTCAAAAAAACTCTGGATCAAGTC C TGAACTCGAGTTCAGGACTTGATCCAGAGTT; MEK1-sh#2-Forward: CCGGAAGGACTCATTACTCTGTGCACTCGAGTGCACAGAGTAATGAGT CCTTTTTTTG and Reward: AATTCAAAAAAAGGACTCATTACTCTG TGCACTCGAGTGCACAGAGTAATGAGTCCTT.…”
Section: Cell Culture and Vectorsmentioning
confidence: 99%
“…There are several lines of evidence suggest an association between the MEK/ERK signaling pathway and liver cancers [12], and the two most common causes of HCC, hepatitis B and C, have viral proteins that activate MEK/ERK signaling [13,14]. Recently, YAP is reported involved in the hepatocarcinogenesis mediated by Hepatitis B virus X protein (HBx), providing evidence that YAP can be also activated by hepatitis viral infection [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have established that HCV core protein can regulate cell signal transduction, such as MAPK-, JAK-STAT-, NF-κB-, AP-1-and SRE-associated pathways [6][7][8] . Hence, it plays important roles in the pathogenesis of HCV persistent infection, as well as HCC.…”
Section: Hepatitis C Virus Core Proteins Derived From Different Quasimentioning
confidence: 99%
“…More interestingly, liver expression of HCV core in transgenic mice results in early steatosis (Moriya et al, 1997) and late HCC development (Moriya et al, 1998). A potential link between modulation of transcription and cell proliferation is provided by the reported ability of HCV core to activate the ERK/SRE signaling pathway in rodent ®broblasts (Tsuchihara et al, 1999), in human epithelial transformed cell lines (Shrivastava et al, 1998) and in a hepatoblastoma cell line Hayashi et al, 2000). Indeed, HCV core has been shown to bind 14-3-3 proteins and to activate Raf-1 .…”
mentioning
confidence: 99%
“…This is particularly relevant in view of the recent demonstration that many HCV chronically infected patients also harbor an`occult' HBV coinfection (Cacciola et al, 1999;Shibata et al, 1999;Tamori et al, 1999) and that HBV-HCV co-infected cirrhotic patients seem to have an increased risk to develop HCC over time (Donato et al, 1998). Moreover, Hayashi et al (2000) have recently shown that Erk1/2 activation by HCV core is enhanced by TPA, that activates Raf1 through PKC and the phosphorylation of Ser 497 and Ser 499 in the Raf1 kinase domain, suggesting that HCV core may act synergistically with other stimuli that activate Raf1 with a di erent mechanism. The ability of HCV core proteins to activate the MAP kinase cascade may contribute, in concert with its ability to protect cells from various apoptotic stimuli (De Francesco, 1999) and with other genetic or environmental factors (Hayashi et al, 1999), to the neoplastic transformation of HCV infected liver cells.…”
mentioning
confidence: 99%